Re-routing in Europe: The Key to Successful Communication as a Truck Driver with Limited Language Competence - Juhász, Dávid (Working Papers in Language Pedagogy, 2013)
Although there are a number of professions that include communication among participants whose native languages are not shared, so far no research has been carried out exploring how Hungarian truck drivers get along in their daily routine with a limited language competence. This paper is based on a qualitative investigation carried out to investigate what kind of language competence Hungarian truck drivers possess, what situations they participate in, what language-based challenges they face, whether they consider their language competence adequate to carry out their daily work and, finally, what other skills and competences they draw on should their language competence prove to be insufficient. The results the interview study show that Hungarian truck drivers measure their foreign languages skills against the tasks they can carry out with their help and that they are able to perform efficiently partly due to the fact that most of the problems they might face are highly predictable and they can prepare for them. The study also reveals that although they consider their language proficiency to be sufficient, should previously avoided problems occur, they draw on a number of communication strategies and tools.